Revelation of causes of colour change in beryllium-treated sapphires - Pichet Limsuwan (2018)
Blue sapphires are treated with Be in oxidizing atmosphere to change the blue colour into yellow. Untreated and Be-treated samples are examined using laser ablation inductively coupled-plasma-mass spectrometry (LA-ICP-MS), electron spin resonance (ESR) and ultraviolet-visible (UV-vis) spectroscopy. The results show that the yellow colouration in Be-heated blue sapphires is not due to Be diffusion from the surface of sapphire. Be behaves as a sole catalyst in this process. We find that the charge transfer between the ferrous (Fe2+) and ferric (Fe3+) is the reason of the colour change. The above conclusions are confirmed by ESR measurements to determine the connections between the Fe3+ions before and after Be-treated heat treatments. © 2008 Chinese Physical Society and IOP Publishing Ltd.